Loss of fibulin-4 results in abnormal collagen fibril assembly in bone, caused by impaired lysyl oxidase processing and collagen cross-linking - Sasaki, Takako; Stoop, Reinout; Sakai, Takao; Heß, Andreas; Deutzmann, Rainer; Schlötzer-Schrehardt, Ursula; Chu, Mon-Li; Von Der Mark, Klaus (Matrix Biology, 2016)
The extracellular matrix protein fibulin-4 has been shown to be indispensable for elastic fiber assembly, but there is also evidence from human mutations that it is involved in controlling skeletal development and bone stability. Fibulin-4 mutations were identified in patients suffering from vascular abnormality and/or cutis laxa, and some of these patients exhibited bone fragility, arachnodactyly and joint laxity. In order to elucidate the role of fibulin-4 in bone structure and skeletal development, we analyzed structural changes in skeletal tissues of Fbln4(-/-) mice. Immunostaining confirmed that fibulin-4 is highly expressed in cartilage, bone, ligaments and tendons. No morphological abnormalities were found in the skeleton of Fbln4(-/-) mice as compared to wild type littermates except forelimb contractures as well as unusually thick collagen fibrils. Furthermore, fibulin-4 deficiency caused enhanced susceptibility of bone collagen for acid extraction, consistent with significantly reduced lysylpyridinoline and hydroxylysylpyridinoline cross-links in bone. In accordance with that, the amount of lysyl oxidase in long bones and calvaria was strongly decreased and proteolytic activation of lysyl oxidase was reduced in fibulin-4 deficient osteoblasts, while addition of recombinant fibulin-4 rescued the activation. The finding suggested that fibulin-4 is important for the proteolytic activation of lysyl oxidase which has a pivotal role in cross-linking of collagen and elastin.
EVALuna2:10209